The oxygen reduction reaction of ordered porous carbon-supported PtSn catalysts. Issue 50 (4th May 2016) - Shen, Chin-Tien; Wang, Kuan-Wen; Tseng, Chung-Jen; Lee, Kan-Rong; Hsueh, Yu-Jui
Abstract : Before and after ADT, the stabilization stems from electronic modification effect of synergistic Sn and OPC addition. Abstract : In this study, ordered porous carbon (OPC) prepared by a template method has been used as the catalyst support for cathodic oxygen reduction reaction (ORR) due to its large surface area and continuous structure. PtSn alloy nanoparticles with a size of 2.7 nm are deposited on OPC by using alcohol reduction method. The synergistic effect of Sn alloying and OPC support can not only modify the surface chemical states of Pt and Sn but also affect the d-band vacancy of Pt. The X-ray photoelectron spectroscopy and X-ray absorption near edge spectroscopy reveal that the oxidation of Pt is suppressed in PtSn/OPC, thus promoting the ORR performance before and after accelerated durability test.